Impact of cadmium, cobalt and nickel on sequence-specific DNA binding of p63 and p73 in vitro and in cells - Adámik, Matej; Bažantová, Pavla; Navrátilová, Lucie; Polášková, Alena; Pečinka, Petr; Holaňová, Lucie; Tichý, Vlastimil; Brázdová, Marie (Biochemical and biophysical research communications, 2015)
Site-specific DNA recognition and binding activity belong to common attributes of all three members of tumor suppressor p53 family proteins: p53, p63 and p73. It was previously shown that heavy metals can affect p53 conformation, sequence-specific binding and suppress p53 response to DNA damage. Here we report for the first time that cadmium, nickel and cobalt, which have already been shown to disturb various DNA repair mechanisms, can also influence p63 and p73 sequence-specific DNA binding activity and transactivation of p53 family target genes. Based on results of electrophoretic mobility shift assay and luciferase reporter assay, we conclude that cadmium inhibits sequence-specific binding of all three core domains to p53 consensus sequences and abolishes transactivation of several promoters (e.g. BAX and MDM2) by 50μM concentrations. In the presence of specific DNA, all p53 family core domains were partially protected against loss of DNA binding activity due to cadmium treatment. Effective cadmium concentration to abolish DNA-protein interactions was about two times higher for p63 and p73 proteins than for p53. Furthermore, we detected partial reversibility of cadmium inhibition for all p53 family members by EDTA. DTT was able to reverse cadmium inhibition only for p53 and p73. Nickel and cobalt abolished DNA-p53 interaction at sub-millimolar concentrations while inhibition of p63 and p73 DNA binding was observed at millimolar concentrations. In summary, cadmium strongly inhibits p53, p63 and p73 DNA binding in vitro and in cells in comparison to nickel and cobalt. The role of cadmium inhibition of p53 tumor suppressor family in carcinogenesis is discussed.
Keywords: těžké kovy; protein p73; Metals, Heavy; Transcriptional Activation; Tumor Suppressor Protein p53; dithiothreitol; Tumor Protein p73; Tumor Suppressor Proteins; Metals; vazba proteinů; Cadmium; kadmium; Humans; nádorové supresorové proteiny; Cobalt; Heavy metals; Edetic Acid; DNA vazebné proteiny; kobalt; Membrane Proteins; Protein Structure, Tertiary; terciární struktura proteinů; Nickel; Cell Line, Tumor; DNA-Binding Proteins; DNA; nádorové buněčné linie; membránové proteiny; kovy; aktivace transkripce; EDTA; nikl; jaderné proteiny; p53 protein family; Nuclear Proteins; Sequence-specific DNA binding; lidé; nádorový supresorový protein p53; Protein Binding; Dithiothreitol